STANDAR KOMPETENSI TUTOR PENDIDIKAN KEAKSARAAN: REFLEKSI DARI PENGEMBANGAN MODEL DI JAYAGIRI - Kusmiadi, Ade (JIV-Jurnal Ilmiah Visi, 2007)
State rules No. 19, 2005 on National Education Standards has defined eight criteria as a reference in developing education in all areas. One criterion is regarding standards on educators and educational personnel. The term educators may refer to teachers, instructors, and tutors. The later is applied to literacy education area in NFE. Tutors are to have background on pedagogy, good personality, good social relationships and be professional. These competencies are of minimum requirements. The article discusses a model on tutor’s competencies which reflect their expected performances, and their supporting subcomponents as well as attached elements.